PERLINDUNGAN HUKUM TERHADAP JUSTICE COLLABORATOR DALAM PERKARA TINDAK PIDANA NARKOTIKA (Studi.Putusan Nomor: 1273/Pid.Sus/2019/PN.Plg.) - Fidelis Bonatua Sihite; Situmeang, Tomson; Panjaitan, Edward ML; Ika Darmika (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Justice Collaborators are suspects, defendants, convicts who cooperate with law enforcement to reveal a certain criminal offense. In narcotics crime Justice Collaborators are used as a tool in uncovering, fighting, organized cases. Justice Collaborator is an extraordinary crime (Extra Ordinary Crime), where the perpetrator needs protection. The formulation of the problem in this study is how the protection, rights and obligations of Justice Collaborators and the analysis of the application of Justice Collaborators in Case Study of Criminal Case Decision Number: 1273/PID.SUS/2019/PN.Plg. This research uses a study with qualitative normative juridical methods, which is research obtained from secondary sources. This research is an analysis that analyzes the protection system, rights, and obligations as a Justice Collaborator by using secondary data, namely Supreme Court Circular Letter No. 04 of 2011 concerning Treatment of Criminal Reporters and Cooperating Perpetrators, and also using other secondary legal materials such as books, journals, and the internet. From the results of this study, it can be concluded that Justice Collaborators are defendants whose interests and protection rights must be applied as perpetrators who reveal an organized crime